Post-Stroke Death Anxiety of a Sample of Stroke Patients at Bethlehem Arab Society for Rehabilitation and Surgery - Kharoufeh, Mirna Mario; Hussein, Ola Ali (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the level of post-stroke death anxiety of a sample of stroke patients, and the differences in their level of death anxiety according to the study variables (gender, age, educational level, stroke re-currency, and the presence of relatives who died with stroke). To achieve the objectives of the study, the analytical descriptive approach was used, applying the death anxiety scale consisting of (24) paragraphs on an available sample of (50) individuals in all departments of Bethlehem Arab society for Rehabilitation. The results of the study showed that the death anxiety level among the sample was moderate. The results also indicated that there were no statistically significant differences at the significance level (≤0.05) in the level of death anxiety after stroke among the stroke sufferers, attributable to the study variables (sex, age, educational level, stroke recurrence and the presence of relatives who died of stroke). In light of these results, the study recommended the design of specialized counseling and treatment programs to reduce the degree of post-stroke death anxiety among patients at Bethlehem Arab Society for Rehabilitation, to enable patients to learn mechanisms for dealing with psychological and physical symptoms.